Paracetamol (acetaminophen) for pain after oral surgery. (13th December 2013) - Coulthard, P.; Bailey, E.; Patel, N.
Abstract Aim To describe the role of paracetamol (acetaminophen) in the management of pain after oral surgery. Materials and methods A review of the literature describing the pharmacokinetics, benefits and harms of paracetamol in terms of systematic review evidence, interactions, use in children, pregnancy and breastfeeding. Results Paracetamol inhibits cyclooxygenase (COX)‐3 isoenzyme and reduces prostanoid release in the central nervous system. The analgesic effectiveness of paracetamol in the control of pain after oral surgery has been shown in a number of clinical trials with a number needed to treat for 1 g paracetamol of 1.87. There are few adverse events, but at toxic doses, harm to the liver may arise and paracetamol poisoning remains the commonest cause of acute liver injury in Europe and North America. Conclusions Paracetamol is an effective analgesic for mild to moderate pain and has an excellent safety record in adults and children. It is also one of the safest analgesics to use if needed during pregnancy and breastfeeding.